A comparative study of socio-demographic characteristics of divorced women and married women in Kano, northern Nigeria - Sulaiman BA; Gambo TM; Dankishiya FS (Ibom Medical Journal, 2025)
Background: Divorce remains a significant global psychosocial challenge, with particularly profound implications in developing nations. The complex interplay of socio-demographic, economic, and cultural factors contributes to marital dissolution, especially in northern Nigeria's unique social context.